Analisis Strukturalisme: Struktur Luar dann Struktur Dalam pada Puisi “Kau” Karya Nuke Hanasasmit - Debora Putriani Br Nainggolan; Visensia Sihite; Sonia Manihuruk; Safinatul Hasanah Harahap (CV. Rayyan Dwi Bharata, 2024)
Puisi